Library Instruction for Graduate Nursing Students: A Scoping Review - Grabowsky, Adelia; Spybey, Katherine (Evidence Based Library and Information Practice)

(untitled) (University of Alberta Library, 2022)
Objective – The number of graduate nursing programs in the U.S. has increased significantly in recent years. This scoping review seeks to examine the range of literature discussing librarian instruction for graduate nursing students to identity the types of studies being published, the characteristics of instructional sessions, knowledge gaps which may exist, and the evidence available for a subsequent systematic review evaluating instructional effectiveness.Methods – Guidelines established by the PRISMA statement for scoping reviews (PRISMA-Scr) were used to conduct this review. Concepts for library instruction and graduate nursing students were searched in six databases as well as Google Scholar. The two authors used titles/abstracts and when necessary, full-text to independently screen identified studies. Conflicting screening decisions were resolved by discussion.Results – Data was extracted from 20 sources. Thirteen of the sources were descriptions of classes or programs, one was a program evaluation, two were mixed methods studies that looked at library use and program support respectively but did not assess instruction, two were surveys of students’ feelings and attitudes about instruction, and two were quasi-experimental studies which included pre-post instruction quizzes. The most popular format for library instruction was online (synchronous or asynchronous) instruction. Most sources did not include information about the timing or duration of instruction. In addition, most sources did not reference instructional theory although a few mentioned aspects of instructional theory such as active learning. Only one source mentioned using a specific model to develop instructional content. While several sources mentioned assessment of student learning, only four studies included the results of assessment.Conclusions – Sources reporting on instruction for graduate nursing students consisted primarily of descriptions of programs or instructional sessions. Many of the descriptive studies lacked essential information such as specifics of format, timing, and duration which would aid replication at other institutions. Only four sources were research studies that evaluated instructional effectiveness.